China, as the Sovereign Creditor of Emerging Markets and Developing Economies - Póra, András; Széplaki, Valéria (Public Finance Quarterly, 2022)
The study’s three main questions are: 1. What trends can be observed in Chinese sovereign lending? 2. How does the contractual setup differ from the Western one? 3. What proposals have been made to mitigate the related risks, and which ones seem feasible? The research relied on recently established databases and regulatory materials. China is the world’s largest sovereign creditor at the moment. Its credit expansion began as early as 2008, well before the official announcement of the intention. Several conditions in its contracts differ from those of the West, which pose a risk relevant to an international debt settlement. Their purpose is twofold: to make a profit secured by strong collaterals and, if necessary, “soft power” influence. On the other hand, China does not use “debt-trap diplomacy”. Any global reform in sovereign debt management needs the involvement of China, but in the longer term, Chinese lending conditions should also ease.